If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -6) + -4n = 16 Reorder the terms: 4(-6 + 3x) + -4n = 16 (-6 * 4 + 3x * 4) + -4n = 16 (-24 + 12x) + -4n = 16 Reorder the terms: -24 + -4n + 12x = 16 Solving -24 + -4n + 12x = 16 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '24' to each side of the equation. -24 + -4n + 24 + 12x = 16 + 24 Reorder the terms: -24 + 24 + -4n + 12x = 16 + 24 Combine like terms: -24 + 24 = 0 0 + -4n + 12x = 16 + 24 -4n + 12x = 16 + 24 Combine like terms: 16 + 24 = 40 -4n + 12x = 40 Add '-12x' to each side of the equation. -4n + 12x + -12x = 40 + -12x Combine like terms: 12x + -12x = 0 -4n + 0 = 40 + -12x -4n = 40 + -12x Divide each side by '-4'. n = -10 + 3x Simplifying n = -10 + 3x
| 87(43)= | | 4v+2v=12 | | 30m+50=20m+100 | | x/5-4=10x-4 | | y=108+16(12) | | 8y+(-2)=22 | | (2x+6)+(5x+4)= | | 7r^2+20r-3=0 | | 8x+6=7x-9 | | 2x+10=-2-4x | | -6z-11=61 | | 20x-16x-160=30x+360 | | y=108+16(11) | | 2X+457= | | 5*(2x-11+17)=52 | | 50-3x=30 | | log1024/5√3 | | 3p-15+(-3p)=-27 | | (4x+1)(7-3x)=0 | | -y^2+2y+x+2=0 | | (5a+3)=14a-29 | | -0.5x+2y=2 | | (1/3)9cu | | 5/7:15/14=6/5 | | ax-by=2 | | -12X+7X=13 | | -3r*4rx+x+12= | | -5=C-10 | | 15n^2-30n=0 | | 9(t-3)+36t=6(t+2) | | 3-(x-4)=2x+5 | | 12s^3+22s^2-70s=0 |